HEXAVALENT CHROMIUM REMOVAL FROM AQUEOUS SOLUTION USING TRICHODERMA VIRIDE - ARASAPPAN SUGASINI,; KALYANARAMAN RAJAGOPAL, (International Journal of Pharma and Bio Sciences, 2015)
Chromium, a toxic heavy metal released by different industries is considered to be one of the environmental pollutants. Fungi being effective in removing heavy metals due to excellent metal binding efficiency, in the present study 23 fungi were isolated from tannery effluent. Out of which Trichoderma viride was taken under study. Chromium biosorption ability of both live and alkali pretreated T. viride was compared and the conditions for chromium removal were also studied. Maximum removal was observed at pH 2, in the initial metal ion concentration of 75 mg/l at 35 oC, biosorbent dose at 1 g for alkali pretreated and 0.4 g for live biomass and contact time at 150 minutes. Under optimum conditions, maximum removal of chromium was 37 mg/g and 18 mg/g for alkali pretreated and live biomass respectively. The change in protein content was analyzed before and after biosorption of chromium and it was observed that the protein content was higher after biosorption. FTIR analysis showed that chromium-binding sites on fungal cell wall would be –OH group, as there was a shift in the stretching frequency.